2001
DOI: 10.2113/gscanmin.39.4.1073
|View full text |Cite
|
Sign up to set email alerts
|

Fe SPECIATION IN WEATHERED PYROCHLORE-GROUP MINERALS FROM THE LUESHE AND ARAXA (BARREIRO) CARBONATITES BY 57Fe MOSSBAUER SPECTROSCOPY

Abstract: The minerals of the pyrochlore group exhibit a large range of chemical composition. The general structural formula can be written as A 2-m B 2 X 6-w Y 1-n •pH 2 O. The occupancy of the eight-fold-coordinated A site can reflect the degree of alteration of the pyrochlore. In unaltered pyrochlore-group minerals, this site is completely filled by Na and Ca, whereas in the altered equivalents, the A site is only partly filled by cations as K, Ba, Sr and Ce. In the literature, the structural formula is systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…At n = 0, A is an eightfold-coordinated cation (mostly Ca and Na, with K, Sr, Ba, Sn 2+ , Pb 2+ , REE 3+ , Y, Sb 3+ , Bi 3+ , U 4+ , and Th 4+ occurring less commonly or in lesser amounts) whereas B is an octahedrally coordinated cation, namely Nb, Ta, and Ti 4+ (or Sb 5+ in the stibiconite mineral group) with minor quantities of Fe 3+ , Sn 4+ , and W 6+ . The X position is mostly occupied by O 2-or, to a lesser extent, OH - (Ercit et al 1993(Ercit et al , 1994Nasraoui and Waerenborgh 2001), whereas Y may be O 2-, OH -, or F -. Pyatenko (1959) was the fi rst to recognize that the pyrochlore structure is a derivative of the fl uorite structure.…”
Section: Introductionmentioning
confidence: 99%
“…At n = 0, A is an eightfold-coordinated cation (mostly Ca and Na, with K, Sr, Ba, Sn 2+ , Pb 2+ , REE 3+ , Y, Sb 3+ , Bi 3+ , U 4+ , and Th 4+ occurring less commonly or in lesser amounts) whereas B is an octahedrally coordinated cation, namely Nb, Ta, and Ti 4+ (or Sb 5+ in the stibiconite mineral group) with minor quantities of Fe 3+ , Sn 4+ , and W 6+ . The X position is mostly occupied by O 2-or, to a lesser extent, OH - (Ercit et al 1993(Ercit et al , 1994Nasraoui and Waerenborgh 2001), whereas Y may be O 2-, OH -, or F -. Pyatenko (1959) was the fi rst to recognize that the pyrochlore structure is a derivative of the fl uorite structure.…”
Section: Introductionmentioning
confidence: 99%
“…Weathered pyrochlore supergroup minerals are commonly hydrated and deficient in A-site cations (Nasraoui & Waerenborgh 2001). Only the B-site lacks deficiencies (Atencio et al 2010).…”
mentioning
confidence: 99%
“…Calculation of other components such as O and OH was done using charge balance and stoichiometry. Nasraoui and Waerenborgh (2001) demonstrated that the oxidation state of Fe can change in secondary pyrochlores and that some Fe 2+ can be present in the B position along with Fe 3+ . However, the amounts of total Fe are very low in all of the secondary pyrochlores, therefore, the iron oxidation state does not have a significant influence on the charge valence.…”
Section: Methodsmentioning
confidence: 99%